Analysis Of The Financing Procedure Assessment Process In Leasing Companies In An Effort To Prevent Bad Debts: A Case Study Of PT. Astra Credit Company Sukabumi - Nugraha, Septiana; Nugroho , Gatot Wahyu; Eriswanto , Elan (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
This research aims to analyze the process of assessing financing procedures at leasing companies in an effort to prevent bad credit, focusing on the case study of PT Astra Credit Company Sukabumi. In the business world, leasing companies play an important role in providing financing solutions for consumers who need goods or vehicles. However, the risk of bad credit is always a challenge that needs to be faced. Therefore, it is important for leasing companies to have good and effective assessment procedures in managing these risks. This research uses qualitative methods with an in-depth case study approach to identify the stages of financing assessment, risk analysis and mitigation strategies implemented by PT Astra Credit Company Sukabumi. Data was obtained through interviews with management, credit assessment staff, and related analysis. The research results show that PT Astra Credit Company Sukabumi has implemented assessment procedures that involve comprehensive credit worthiness analysis, including verification of prospective consumer data, analysis of payment capabilities, and use of a comprehensive credit scoring system. Apart from that, the company also implements prevention strategies through regular monitoring and strict risk mitigation measures. This research provides an important contribution in understanding financing assessment practices in leasing companies and provides recommendations for improving assessment procedures to prevent bad credit more effectively.